Computational screening and characterization of putative vaccine candidates of Plasmodium vivax. Issue 8 (2nd August 2016) - Nanda Kumar, Y.; Jeyakodi, G.; Gunasekaran, K.; Jambulingam, P.
Abstract : Plasmodium vivax is the most prevalent species of malaria affecting millions of people annually worldwide and demands effective interventions to develop a successful vaccine. In this milieu, we have dedicated noteworthy efforts to characterize the proteome of P. vivax to give a lead for the epitope-based vaccine development. Membrane proteins of P. vivax were collected from SWISS PROT database and 10 antigenic proteins were identified among them by in silico analysis using multiple servers. T-cell and B-cell epitopes were identified and their immunity was assessed. Their ability to trigger humoral and cell-mediated responses was determined. Three dimensional models were constructed for the antigenic proteins using Modeller, Phyre2, and Modloop tools and their quality was validated using PROCHECK and ProSA-web validation servers. Further, the binding affinity and molecular interactions of these antigenic proteins were characterized by performing protein–protein docking against transmission-blocking anti-malaria antibody Fab2A8 (PDB ID: 3S62) using Z-dock module of Discovery Studio 4.0. The presence of potential B & T-cell epitopes, major histocompatibility complex-binding sites, and their efficient interactions with Fab2A8 antibody suggests the use of predicted antigenic proteins for the construction of multi-epitope peptide vaccine against P. vivax .